Propuesta de diseño implementación y gestión de operaciones de biodigestores en la empresa Viña Castilla - Carrasco Bravo, Victor Bruno (2016)
There is a growing chance of developing non-conventional renewable resources in our country. Much of these resources are generated in production activities such as the cases of livestock, poultry, timber and wine companies to name a few. These businesses have potential for generating renewable resources, but are seen as waste in the production process. To promote the use of these wastes as energy resources, the government have approved the creation of new energy plants like biomass or biogas, among others throughout the country. In addition, they have generated technical standards that allow organizations to use their own waste to generate the necessary energy that enables them to reduce their production costs. This improvement proposal seeks to establish a management model to properly exploit the waste generated in the production of Pisco breaks into a wine. To do this, using machines that allow the conversion of organic waste into non-conventional energy sources it will be defined. Moreover, the economic impact of the proposal on the company demonstrating the viability of the same will be evaluated. Finally leave the steps for any other company in the same field can take the research and assess the possibility of creating their own biogas generation machinery.